SINAIS DO TRANSTORNO DO ESPECTRO AUTISTA: FORMAÇÃO DE PROFESSORES E RASTREIO PRECOCE NA EDUCAÇÃO INFANTIL - RATUCHNE, PALOMA APARECIDA OLIVEIRA (2023)
Since the 1990s, Brazilian legislation has guaranteed the right to equal access and permanence in education, across all levels, for people who are Targeted for Special Education (PAEE). Part of this group is affected by Autism Spectrum Disorder (ASD), which is a neurodevelopmental disorder characterized by deficits in communication and social interaction, with the presence of repetitive and restrictive behaviours, manifested up to 36 months of age. In this scenario, this study, which is part of the Education, Culture and Diversity research line and is part of the Interdisciplinary Study and Research Group on Human Development and Education (GIEDH), is based on the assumption that teachers' understanding of the unique characteristics of ASD makes it possible to identify and intervene early with children on the spectrum. As Early Childhood Education (EI) is the first stage of Basic Education, whose function is the integral development of the child in physical, psychological, social and intellectual aspects, the main objective of this research was to plan, apply and evaluate training for teachers at Municipal Early Childhood Education Centers (CMEI) in the city of Guarapuava-PR, with an emphasis on identifying signs of ASD and proposing inclusive pedagogical practices for children up to 36 months of age. The methodology adopted was action research from the perspective of the cultural-historical approach, and the data analysis was qualitative, descriptive and exploratory. Two instruments were used to generate data: (a) questionnaires - A and B - applied before and after the proposed training, in order to identify the teachers' understanding of the subject, their anxieties, difficulties and facilities; and (b) the M-CHAT-R/F© scale used to check whether the training helped the teacher to assimilate the signs attributed to ASD, as well as screening children with signs of ASD at the CMEI. Seven CMEIs took part in the study, comprising 35 teachers, 4 supervisors, 2 directors and 22 children. The data was processed using Bardin's (1977; 2011) content analysis. As a result, there was a significant increase in the perception of signs attributed to ASD after the training, showing that the teachers who identified signs in young children were in favor of early intervention even without a diagnosis, as well as being assertive in the referrals given to families. Having a guiding instrument, the participants were more confident in referring children for early screening, and one of the children was diagnosed immediately after undergoing screening. Another point was that the questionnaires revealed difficulties, with more than 50% of the teachers reporting no facilities. The main limitations or possibilities in caring for children with ASD pointed out by the teachers were related to social behavior and language, pedagogical actions and learning, and family support and human/pedagogical resources. It was concluded that challenges cross the education of children and childhood(ies), especially children with ASD, which is why providing continuing and in-service training, as well as tools to guide pedagogical practices with a view to the child's integral development, are essential, in addition to promoting effective public policies for the implementation of Specialized Educational Care (SEA) in EI.